Early Vaccination With Bacille Calmette-Guérin-Denmark or BCG-Japan Versus BCG-Russia to Healthy Newborns in Guinea-Bissau: A Randomized Controlled Trial. (3rd November 2019) - Schaltz-Buchholzer, Frederik; Bjerregaard-Andersen, Morten; Øland, Christian Bjerregård; Golding, Christian; Stjernholm, Elise Brenno; Monteiro, Ivan; Aaby, Peter; Benn, Christine Stabell
Abstract: Background: Bacille Calmette-Guérin (BCG) vaccination remains a cornerstone against tuberculosis. Randomized controlled trials (RCTs) have demonstrated that BCG-Denmark lowers all-cause mortality, but a recent RCT found no effect of BCG-Russia. Observational studies indicate that the genetically divergent BCG strains have different effects. Methods: This was a parallel-group, open-label RCT conducted at the National Hospital in Guinea-Bissau. Healthy neonates were randomized 1:1 to BCG-Denmark (2851 randomized, 2840 analyzed) vs BCG-Russia (2845 randomized, 2837 analyzed). We hypothesized that BCG-Denmark would reduce morbidity (primary outcome) and mortality while inducing more BCG reactions and purified protein derivative (PPD) responses (secondary outcomes). Halfway through the trial, production of BCG-Denmark was halted, and the trial continued comparing BCG-Japan (3191 neonates randomized, 3184 analyzed) with BCG-Russia (3170 randomized, 3160 analyzed). Mortality and morbidity data were collected by telephone, at home visits, and at the National Hospital and assessed in Cox models providing 6-week mortality rate ratios (MRRs) and hospitalization incidence rate ratios (IRRs). Results: By age 6 weeks, there were 140 and 130 admissions among neonates vaccinated with BCG-Denmark and BCG-Russia, respectively (IRR, 1.08 [95% confidence interval CI, .84–1.37]). For BCG-Japan, there were 185 admissions vs 161 admissions for BCG-Russia (IRR, 1.15 [95% CI, .93–1.43]). The 6-week mortality did not differ: BCG-Denmark/BCG-Russia (MRR, 1.15 [95% CI, .74–1.80]); BCG-Japan/BCG-Russia (MRR, 0.71 [95% CI, .43–1.19]). BCG-Denmark and BCG-Japan induced more BCG scars and PPD reactions than BCG-Russia. Conclusions: BCG strains did not affect morbidity. BCG-Denmark and BCG-Japan were more immunogenic than BCG-Russia by the measures traditionally viewed as surrogates for successful immunization. The implications of strain differences for tuberculosis protection and overall health warrant further study. Clinical Trials Registration: NCT02447536. Abstract : In a randomized controlled trial from Guinea-Bissau evaluating effects of different Bacille Calmette-Guerin (BCG) vaccine strains on overall health, BCG strains did not affect morbidity or mortality. BCG-Japan and BCG-Denmark produced more BCG reactions, more purified protein derivative reactivity, and more adverse events than BCG-Russia.